2022
DOI: 10.3390/ijerph19031741
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Labor Pain Control and Women’s Satisfaction

Abstract: Introduction: Pain experienced during labor is a symptom of contractile activity and is a physiological feature of the uterus that occurs at the appropriate stages of labor. For the majority of women, labor pain is the most severe pain they will ever experience, and therefore should be relieved. Objective: (1) To evaluate labor pain intensity before and after using non-pharmacological and pharmacological interventions; (2) to assess women’s satisfaction of labor pain management. Methods: A multicenter cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Epidural anesthesia (EA), as one of the most common methods of labor analgesia, has the advantages of strong analgesic effect, fixed analgesic plane, long duration, and easy control of drug dosage [ 5 , 6 ]. It can effectively relieve labor pain, and the effect is stronger than that of general opioid anesthesia [ 7 , 8 ]. However, studies [ 9 , 10 ] have found that EA can prolong the second stage of labor.…”
Section: Introductionmentioning
confidence: 99%
“…Epidural anesthesia (EA), as one of the most common methods of labor analgesia, has the advantages of strong analgesic effect, fixed analgesic plane, long duration, and easy control of drug dosage [ 5 , 6 ]. It can effectively relieve labor pain, and the effect is stronger than that of general opioid anesthesia [ 7 , 8 ]. However, studies [ 9 , 10 ] have found that EA can prolong the second stage of labor.…”
Section: Introductionmentioning
confidence: 99%
“…There are pharmacological and non-pharmacological options to treat pain during vaginal delivery (11)(12)(13). The list of nonpharmacological options is large with strategies such as breathing and relaxation techniques, applying heat or cold, water immersion (shower, bathtub), touch and massage, acupuncture, transcutaneous electrostimulation, music and aromatherapy.…”
Section: The Global Pain Divide In Obstetricsmentioning
confidence: 99%
“…[Citation: kakar, P.K., Anila, khan, A.G.M., Sindhu, S. ( 2023 hydrotherapy, massage, visualization, positioning, and aromatherapy (Czech et al, 2018). Each technique targets distinct aspects of pain perception and coping mechanisms to reduce pain intensity, enhance relaxation, and foster a sense of control and empowerment during labor (Jones et al, 2012;Smith et al, 2018). Multiple studies have examined the efficacy of nonpharmaceutical pain management techniques in enhancing childbirth experiences.…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation should consider pain reduction, maternal satisfaction, neonatal health, and long-term consequences on post-partum recovery. Understanding the advantages and disadvantages of these techniques will assist healthcare providers, policymakers, and expectant mothers make informed decisions (Hu et al, 2021;Pietrzak et al, 2022). The objective of the research evaluating the efficacy of nonpharmacological pain managing modus operandi during labor and delivery is to fill several knowledge gaps.…”
Section: Introductionmentioning
confidence: 99%